Caregiver burden in Alzheimer's disease: Moderation effects of social support and mediation effects of positive aspects of caregiving. (1st June 2018) - Wang, Zhixin; Ma, Caiyun; Han, Hongjuan; He, Runlian; Zhou, Liye; Liang, Ruifeng; Yu, Hongmei
Abstract : Objectives: Although there are many studies on the relationship between patient‐related factors and negative caregiver outcomes, the specifics of this relationship are poorly understood. We aimed to examine whether caregiver social support moderated the relationship between patient factors and negative outcomes for caregivers of community‐dwelling older adults with Alzheimer's disease (AD), and whether positive aspects of caregiving mediated this relationship. Methods: We conducted a cross‐sectional study of patients diagnosed with AD from 2 hospitals and 3 communities in Taiyuan, China, and their caregivers. Latent moderated structural equations and the bias‐corrected percentile bootstrap method were used to estimate the parameters of moderating and mediating effects, respectively. Results: Social support significantly moderated the effects of AD patient cognitive function ( P  < 0.001) and depression ( P  = 0.001) on caregiver burden. Positive aspects of caregiving completely mediated the association between patient depression and caregiver burden ( P  = 0.006), caregiver anxiety ( P  = 0.007), and caregiver depression ( P  = 0.034). Conclusions: The findings identify social support as a moderator and positive aspects of caregiving as a mediator of the relationship between patient‐related factors and negative caregiver outcomes. The results suggest that health care providers must offer more effective social support for caregivers. In addition, prompt identification of patient and caregiver emotional states could help to improve quality of life.